HUBUNGAN DUKUNGAN KELUARGA DAN TENAGA KESEHATAN DENGAN KEPATUHAN MINUM OBAT PADA ODS DI PUSKESMAS SUNGAI SARIK. - Yuderna, Vivi; Eni, Rosmi (Ensiklopedia of Journal, 2024)
Abstract: Mental Health is a condition where an individual can develop physically, mentally, spiritually and socially so that the individual is aware of his own abilities, can deal with pressure, can work productively, and is able to contribute to his community without any mental disturbance. ODS (People with Schizophrenia) is a mental disorder characterized by very basic deviations and differences in thoughts, accompanied by unnatural emotional expressions. The research was conducted in July-August 2023 at the Sungai Sariak health center. The research sample was 48 people with a sampling technique using total sampling. The statistical test used Chi Square for the degree of significance (p value < α 0.05), with a P value of 0.010. The research results found that the majority (68.2%) had poor family support and the majority (65%) of staff support was poor. There is a relationship between family support and health workers and compliance with taking medication at the Sungai Sariak Community Health Center 2023Keywords: Family support, health worker support, ODS